1992
DOI: 10.1002/ijc.2910500506
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus formation in peripheral‐blood lymphocytes from smokers and the influence of alcohol‐ and tea‐drinking habits

Abstract: In recent years, studies on the genotoxic effects of smoking and its modifying factors have been widely followed with interest. In this report, frequencies of micronuclei (MNF) in peripheral-blood lymphocytes in 220 healthy smokers have been detected by the micronucleus test by finger-skin puncture, which needs only 1 to 2 drops of peripheral blood. On the basis of analysis of matched-pair data, the modifying effects of alcohol and tea are discussed. Our results show that (I) smoking significantly increases MN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…This effect was also observed in other cell types. 15,25,36,37,50,51 The observation that the heaviest smokers showed a higher number of MNs than nonsmokers supports this suggestion and could indicate a dose-dependent effect. This suggestion is supported by the observation that MN occurrence in nonsmokers and smokers of a few cigarettes per day was not different.…”
Section: Discussionsupporting
confidence: 69%
“…This effect was also observed in other cell types. 15,25,36,37,50,51 The observation that the heaviest smokers showed a higher number of MNs than nonsmokers supports this suggestion and could indicate a dose-dependent effect. This suggestion is supported by the observation that MN occurrence in nonsmokers and smokers of a few cigarettes per day was not different.…”
Section: Discussionsupporting
confidence: 69%
“…Chromosomal damage can be measured using classical cytogenetic methods, micronuclei formation (Schmid, 1975;Xue et al, 1992), COMET (Poli et al, 1999;Speit and Hartmann, 1999), fluorescent in situ hybridization, or PCR methods assessing loss of heterozygosity (using tandem repeats or comparative genomic hybridization) where the latter two methods can be used for morphologically appearing cells. Use of mutations in reporter genes, such as HPRT (Bailar, 1999;Hou et al, 1999) or GPA have been used, but it is better to identify mutation rates in cancer susceptibility genes such as p53 (Brennan et al, 1995;Valkonen and Kuusi, 1998) or K-ras (Scott et al, 1997;Slebos et al, 1991;Valkonen and Kuusi, 1998;Yakubovskaya et al, 1995).…”
Section: Pathobiological Effects and The Clues To Etiologymentioning
confidence: 99%
“…These studies demonstrated that either oral or topical administration of green tea or its major chemical constituent, epigallocatechin gallate, prevented tumor initiation and promotion [8,16]. In human subjects, tea consumption has been shown to decrease micronucleus formation induced by smoking [29]. HPLC analysis of green tea has shown it to be composed of several polyphenols (as much as 30% by dry weight), most of which are catechins: epigallocatechin gallate (15.1%), epigallocatechin (6.9%), epicatechin gallate (3.0%), epicatechin (1.8%), and caffeine (8.1%) [30].…”
Section: Discussionmentioning
confidence: 96%